THE EFFECT OF FERULA EXTRACT ON THE ACTIVITY OF DIGESTIVE ENZYMES - Nozgul F. Qiyomova (Journals Park Publishing, 2023)
It is known that the use of medicinal plants has taken a leading place in the world health system. Currently, the results of research and their use of medicinal plants in the treatment of diseases are increasing. Medicinal herbs or plants are an important potential source of therapeutic or curative agents. This article focuses on the knowledge of medicinal uses of plants and the role, contribution and benefits of medicinal plants against diseases of public health importance.
Keywords: Illness, medicinal plants, digestive tract, therapeutic.